Threefold IPSS-M reclassification outperforms original stratification in predicting post-transplant outcomes for MDS patients - Hongru Chen; Shan Jiang; Ruowen Wei; Ao Zhang; Xiena Cao; Wei Shi; Linghui Xia (Cell Transplantation)
The predictive performance of the Molecular International Prognostic Scoring System (IPSS-M) for high-risk myelodysplastic syndromes (MDS) patients undergoing transplantation remains uncertain. We retrospectively analyzed 86 MDS patients who underwent allogeneic hematopoietic stem cell transplantation (allo-HSCT) at our center from 2016 to 2023. According to IPSS-M, patients were classified as Low ( n = 3), Moderate-Low ( n = 9), Moderate-High ( n = 15), High ( n = 28), and Very-High risk ( n = 31). The IPSS-M did not demonstrate good prognostic accuracy for overall survival (OS) ( P = 0.227) and disease-free survival (DFS) ( P = 0.095) in these 86 patients. We then divided the patients into three groups based on their IPSS-M scores: IPSS-M < 0.56 ( n = 28), IPSS-M 0.56–1.75 ( n = 30), and IPSS-M>1.75 ( n = 28). There was a significant difference in the long-term OS ( P = 0.010) and DFS among the three groups ( P < 0.001). This indicates that, based on the original IPSS-M scores, we may be able to find a more precise risk stratification for high-risk MDS patients undergoing allo-HSCT. Compared with TP53 wild-type and TP53 monoallelic mutations, TP53 biallelic mutations have a significant negative impact on OS and DFS ( P = 0.016, P = 0.006). It is crucial to identify TP53 allelic status at diagnosis to distinguish these patients and determine the need for early involvement in clinical trials.